Validity and Reliability of Instruments: Students' Perception of Google Classroom and Interest in Learning Islamic Religion - Alfiyah, Nur; Chalisah, Naura Diny; Zuhriyah, Indah Aminatus (LPPM Universitas Negeri Jakarta, 2025)
The validity and reliability of measurement instruments are important aspects of educational evaluation to ensure accurate and reliable results. Without instruments that meet these standards, evaluation results risk being irrelevant to learning objectives. This study aims to analyze the external validity and reliability of questionnaire instruments for students' perceptions of Google Classroom and interest in religious studies at SMP Islam Ngoro. A quantitative approach was used in this study, with Pearson Product Moment analysis and Cronbach Alpha as statistical methods. The results showed that on variable X, of the 20 items analyzed, there were 11 valid items and 9 invalid items, with a reliability of 0.891. Meanwhile, on variable Y, there were 9 valid items out of 20 items, with a reliability of 0.787 other items were deleted. The instruments on both variables were declared reliable because they met the reliability criteria (value >0.6). This study contributes to ensuring the quality of accurate evaluation instruments, so that they can support the implementation of technology-based learning such as Google Classroom.